Factors associated with spontaneous abortion: a systematic review - Oliveira,Maria Tânia Silva (2020)
Abstract Objectives: to compile studies produced regardinggenetic and non-genetic risks factors associated with occurrence of spontaneous abortion. Methods: it talks about a systematic review article, with studies between January of 2008 to November of 2018 according to SciELO, PubMed, Lilacs and BVS. Results: in total, 567 articles were found. After applying the definedeligibility criteria, 44 articles made part of the review, being the majority published on Asia between 2008 and 2011, and 10 articles published on Brazil. Not genetic causes like sociodemographic factors and healthy state were among the most associated conditions of spontaneous abortion. Asiatic continent had predominance about the correlation of spontaneous abortion with factors related to life style like obesity, smoking and labor activities, on the other hand, in the Americas, causes related to sociodemographics factors like low pay and low studies are high-lighted. Conclusions: the risk factors change about the occurrence region, being important to make local studies capable of subsidize the implantation of public politics and to reduce abortions.